Islamic Religious Education Teachers' Strategy in Using Multimedia to Increase Students' Learning Motivation at the Ahlussunnah Waljama'ah Integrated Vocational High School in Muaro Bungo - Hasanah, Zetnatul; Kusnadi, Edy; Jannah, Siti Raudhatul (Continuous Education: Journal of Science and Research, 2025)
This study aims to identify and analyze the strategies implemented by Islamic Religious Education (PAI) teachers in the use of multimedia to improve students' learning motivation and explain the process of using multimedia strategies in learning, and find out the supporting and inhibiting factors faced in the learning process, both teachers and students to improve students' learning motivation with multimedia usage strategies. The purpose of this study is to improve students' learning motivation with the use of multimedia, and to improve teachers' ability and understanding to understand various learning strategies that can be used to create a more effective and efficient learning process. This research is a qualitative research based on descriptive conducted at the Ahlussunnah Wal Jama'ah Integrated Vocational High School Muaro Bungo. Data collection techniques using observation, interview, documentation techniques. This study produced three things, namely: (1) explaining Islamic Religious Education Learning why it has not been optimal in the learning process which has an impact on learning motivation. (2) Implementation of Islamic religious education teacher strategies in the use of multimedia, teachers utilize various multimedia platforms such as presentations, interactive videos which aim to convey lesson materials in a more interesting and easily understood way by students.